Analisis Faktor – Faktor yang Menghambat Kinerja Aparat Desa dalam Memberikan Pelayanan kepada Masyarakat di Desa Watutoa Kecamatan Marioriwawo Kabupaten Wajo - Iwan Mamminanga; Andi Supriadi; Burhanuddin Burhanuddin (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study aims to analyze the performance of village government officials in providing services to the community in Watutoa Village, Marioriwawo District, Soppeng Regency. Village officials play a crucial role in delivering optimal services to the public. To achieve this, several supporting and hindering factors are needed, including external factors such as limited resources, government policies, and social environment, as well as internal factors like the skills and knowledge of officials, motivation and commitment, and the systems and procedures used. The purpose of this study is to analyze the factors that hinder the performance of village officials in providing services to the community in Watutoa Village, as well as to identify the supporting factors that facilitate the implementation of services. This research employs a descriptive qualitative method with a community study design. Data were collected through interviews, observations, and documentation. The research participants included the officials of Watutoa Village (the head of the village and the head of sections) and the community members who had received services from the village officials. The results of the study indicate that, overall, the performance of village officials is quite good. However, there are several areas that need attention, such as limited resources, where digital services have not yet been optimized. Although government policies regarding attendance, working hours, sanctions, and training have been effective, there are still areas that need improvement. Infrastructure is sufficiently adequate to support the smooth delivery of services, but the technical skills and utilization of technology by village officials need to be enhanced. Furthermore, the motivation and commitment of the officials in delivering services should be strengthened. The existing service systems and procedures are not fully efficient, so continuous evaluation and improvement are necessary to enhance the quality of services in the future.